CITRIC ACID FORMULATION ON THE QUALITY OF PURPLE EGGPLANT (SOLANIUM MELONGENAL) JAM AS AN EFFORT TO FOOD DIVERSIFICATION (CITRA : International Journal of Community service, Informatics, Technology, Research in education, Art and humanities, 2022)
Purpose analyzed the effect of acid formulation on the quality of color, aroma, texture and taste of purple eggplant jam (Solanium melongena L). The method used in this research is an experimental method using a completely randomized design (CRD) with the addition of citric acid treatment with different concentrations. Each treatment was repeated 3 times. The data obtained were processed by Analysis of Variety (ANOVA). The favorite level sensory test carried out included color, taste, aroma and texture. Overall the level of preference for the eggplant jam. The treatment that had the most extensive and balanced radar between color, taste, aroma and texture and had a high average value was treatment B (eggplant porridge + 2% citric acid) with an average value of 3.92 (liked). Based on the analysis of sensory tests and discussion, it can be concluded that there is an effect of citric acid formulation on the quality of eggplant jam. The citric acid formulation with the addition of 2% citric acid to the eggplant pulp was the most popular formulation by panelists in terms of color, taste, aroma, and texture with a total of 15.66 and an average of 3.92.
Keywords: Jam; Eggplant; Citric Acid